Physicochemical analysis of the blue agave - Lavado Soto, Mooner (2016)
In rural areas of Huancavelica, Huánuco, Ayacucho, Apurimac and Cajamarca. There is an abundant natural resource called blue sisal. There is information that in the southern departments the sisal juice is processed handmade to obtain honey and brown sugar, which are used as a sweetener. Given this situation, it is needed a blue sisal juice physicochemical analysis to identify some properties, mainly the content of inulin having dietary properties. Experimental tests show that this juice found in natural resource contains high content of inulin and total solids (fructose, glucose and others). Based on the above, the industrial processing is feasible; contributing in this way to improve the standard of living of the rural population where this natural resource is abundant.